Nationwide experiences with trough levels, durability, and disease activity among inflammatory bowel disease patients following COVID-19 vaccination - Tamás Resál; Péter Bacsur; Miklós Horváth; Kata Szántó; Mariann Rutka; Anita Bálint; Anna Fábián; Renáta Bor; Zoltán Szepes; János Fekete; Klaudia Farkas; Pál Miheller; et al. (Therapeutic Advances in Gastroenterology, 2023)
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has complicated the management of inflammatory bowel diseases (IBD). Objectives: This study aimed to assess the efficacy of different anti-SARS-CoV-2 vaccines under different treatments in IBD patients and identify predictive factors associated with lower serological response, including anti-tumor necrosis factor (anti-TNF) drug levels. Design: A prospective, double-center study of IBD patients was conducted following messenger ribonucleotide acid (mRNA) and non-mRNA anti-SARS-CoV-2 vaccination. Methods: Healthy control (HC) patients were enrolled to reduce bias. Baseline and control samples were obtained 14 days after the second dose to assess the impact of conventional and biological treatments. Clinical and biochemical activity, serological response level, and anti-TNF drug levels were measured. Results: This study included 199 IBD (mean age, 40.9 ± 12.72 years) and 77 HC participants (mean age, 50.3 ± 12.36 years). Most patients (76.9%) and all HCs received mRNA vaccines. Half of the IBD patients were on biological treatment (anti-TNF 68.7%). Biological and thiopurine combined immunomodulation and biological treatment were associated with lower serological response ( p  < 0.001), and mRNA vaccination promoted better antibody levels ( p  < 0.001). Higher adalimumab levels caused lower serological response ( p  = 0.006). W8 persistence of anti-SARS-CoV-2 level was equal in IBD and HC groups. Vaccination did not aggravate clinical disease activity ( p  = 0.65). Conclusion: Anti-SARS-CoV-2 vaccination is considerably efficacious in IBD patients, with mRNA vaccines promoting better antibody levels. The negative impact of combined biological treatment, especially with high adalimumab drug levels, on serological response to vaccination should be considered. Although midterm durability of vaccination is encouraging, more data are needed to expand the existing understanding on this issue.